2021
DOI: 10.1038/s41467-021-23217-6
|View full text |Cite
|
Sign up to set email alerts
|

FKRP-dependent glycosylation of fibronectin regulates muscle pathology in muscular dystrophy

Abstract: The muscular dystrophies encompass a broad range of pathologies with varied clinical outcomes. In the case of patients carrying defects in fukutin-related protein (FKRP), these diverse pathologies arise from mutations within the same gene. This is surprising as FKRP is a glycosyltransferase, whose only identified function is to transfer ribitol-5-phosphate to α-dystroglycan (α-DG). Although this modification is critical for extracellular matrix attachment, α-DG’s glycosylation status relates poorly to disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 51 publications
(51 reference statements)
1
36
0
Order By: Relevance
“…Since our findings indicate that genes associated with ECM matrix receptor interaction and focal adhesions are dysregulated, we speculate that LGMDR9 mutations may also lead to a disruption in extracellular membrane binding. Interestingly, this is in line with recent data proposing that FKRP acts as a stabilizer of Fibronectin-Collagen 1 binding (Wood et al, 2021).…”
Section: Molecular Characterization Of Patient-specific Fkrp Mutant Myotubessupporting
confidence: 91%
“…Since our findings indicate that genes associated with ECM matrix receptor interaction and focal adhesions are dysregulated, we speculate that LGMDR9 mutations may also lead to a disruption in extracellular membrane binding. Interestingly, this is in line with recent data proposing that FKRP acts as a stabilizer of Fibronectin-Collagen 1 binding (Wood et al, 2021).…”
Section: Molecular Characterization Of Patient-specific Fkrp Mutant Myotubessupporting
confidence: 91%
“…Although this remains to be established, α-DG is the only O-mannosylated protein that has been extensively studied so far [80]; therefore, the possible existence of other proteins containing very similar M3 core structures cannot be ruled out. Recently, it has been reported that indeed FKRP directs sialylation of fibronectin at the muscle basement membrane, influencing the overall stability of sarcolemma in muscular dystrophy and therefore strongly suggesting the existence of multiple target/pathways, alternative to DG, affected by the 'M3' enzymes [81] The very high degree of conservation observed in Chordata strengthens the evidence that these 13 enzymes are important for muscle stability (figure 2). All considered, such remarkable conservation of the enzymatic cascade underlies the overall importance of α-DG carbohydrates for royalsocietypublishing.org/journal/rsob Open Biol.…”
Section: Conservation and Specificity Of The M3 Core Enzymatic Cascadementioning
confidence: 54%
“…Although this remains to be established, α-DG is the only O-mannosylated protein that has been extensively studied so far [ 80 ]; therefore, the possible existence of other proteins containing very similar M3 core structures cannot be ruled out. Recently, it has been reported that indeed FKRP directs sialylation of fibronectin at the muscle basement membrane, influencing the overall stability of sarcolemma in muscular dystrophy and therefore strongly suggesting the existence of multiple target/pathways, alternative to DG, affected by the ‘M3’ enzymes [ 81 ]…”
Section: Resultsmentioning
confidence: 99%
“…[7] In a zebrafish model of fkrp gene mutation, recent work has uncovered a MBM failure resulting from aberrant sialylation of fibronectin. [8] Upon muscle development, fibronectin is a key ligand for the earliest F I G U R E 1 The Dystrophin-associated Glycoprotein Complex-Muscle Basement Membrane axis (DGC-MBM) and Dystroglycan protein structure. (A) Schematic representation of α-Dystroglycan biosynthesis and the DGC-MBM protein components and ligands in the muscle cell.…”
Section: Introductionmentioning
confidence: 99%